Сучасна зарубіжна юридична освіта: історикоправове дослідження (на прикладі США, Великобританії і ФРН) - Проскурняк, Олег Георгійович (Чернівецький національний університет імені Юрія Федьковича, 2019)
У дисертації на основі аналізу нормативно-правових актів, вітчизняної та зарубіжної наукової літератури досліджено основні чинники та тенденції розвитку сучасної зарубіжної юридичної освіти, розкрито особливості їх реалізації в США, Великобританії та ФРН. З-поміж чинників виокремлено зростання соціального престижу юридичної професії і розширення доступу до юридичної освіти; з-поміж тенденцій – реформування моделей юридичної освіти, оптимізацію національних мереж правничих шкіл, прагматизацію зарубіжної юридичної освіти і підвищення ефективності підсумкової атестації юристів. Зроблено висновок, що сучасна юридична професія змогла реалізувати в собі два взаємодоповнюючі принципи: єдності і диференціації. Розвиток інтеграційних процесів у сучасному суспільстві детермінував необхідність існування загальних філософських та інституційних основ юридичної професії. Водночас, кожна правова система під впливом національних традицій зберегла власну специфіку у структурі і розумінні юридичної професії. В диссертации на основе анализа нормативно-правовых актов, отечественной и зарубежной научной литературы исследованы основные факторы и тенденции развития современного зарубежного юридического образования, раскрыты особенности их реализации в США, Великобритании и ФРГ. В качестве факторов определено рост социального престижа юридической профессии и расширение доступа к юридическому образованию; как тенденции - реформирование моделей юридического образования, оптимизация национальных сетей юридических школ, прагматизация зарубежного юридического образования и повышение эффективности итоговой аттестации юристов. Сделан вывод, что современная юридическая профессия смогла реализовать в себе два взаимодополняющих принципа: единства и дифференциации. Развитие интеграционных процессов в современном обществе детерминировал необходимость существования общих философских и институциональных основ юридической профессии. В то же время, каждая правовая система под влиянием национальных традиций сохранила свою специфику в структуре и смысле юридической профессии. In the dissertation on the basis of the analysis of normative legal acts, domestic and foreign scientific literature the basic factors and tendencies of development of modern foreign legal education are investigated, the peculiarities of their realization in the USA, Great Britain and Germany are revealed. The factors that determine the growth of the social prestige of the legal profession and the increased access to legal education; as tendencies – reform of models of legal education, optimization of national networks of law schools, pragmatization of foreign legal education and increase of efficiency of final certification of lawyers. It is concluded that the modern legal profession has been able to implement two complementary principles: unity and differentiation. The development of integration processes in modern society has determined the need for the existence of common philosophical and institutional foundations of the legal profession. At the same time, each legal system under the influence of national traditions has retained its own specifics in the structure and understanding of the legal profession. The growing role of lawyers is justified by the complication of social infrastructure, the development of the legal status of a person, the expansion of rights and freedoms, the jurisprudence of modern society, which reflects a common tendency for all developed countries to expand the subject of legal regulation, increase the political influence of holders of law degree. The criteria for access to legal education are classified into educational and social. Admission to US law schools requires any undergraduate education. In the UK and Germany, the enrollment of students is carried out on the basis of schooling. The only social barrier to access to legal education is tuition fees. Reforming the content of legal education in its most general form concerns models of legal education. In the US, lawyers are trained in 220 law schools, in the UK – 97, in Germany – 44 universities. The structure of legal education, which includes the duration of studies, its division into cycles, courses, semesters and trimesters, is investigated. Pragmatization of legal education is manifested in the practical orientation of the educational process, its orientation on the individual interests of students, the development of their practical skills. Such a new form of practical training of lawyers as law clinics has been investigated. The final form of practical training of lawyers in the UK and Germany – internships is analyzed. The solicitor's internship lasts two years, the barrister's internship – 1 year, the referendariat – two years. In the US, there is no postgraduate education. In Germany, there is a single standard for all law school graduates, which includes two state exams. In the United States, admission to law is through bar examination. In the UK, separate qualification tests are conducted for solicitors and barristers. Their purpose is not to test knowledge, but to test readiness for independent legal practice.
Современное зарубежное юридическое образование: историко-правовое исследование (на примере США, Великобритании и ФРГ)
Contemporary foreign legal education: a historical and legal study (for example, USA, UK and FRG)
Keywords: юридична освіта; правнича школа; юридичний факультет; прагматизація юридичної освіти; юридична професія; юрист; референдаріат; юридическое образование; юридическая школа; юридический факультет; прагматизация юридического образования; юридическая профессия; юрист; референдариат; law education; law school; law school; pragmatization of legal education; legal profession; lawyer; referendariat; 340.5; 34.023; 34.09